Vibration Characteristic of Difference Rail Crack Via 3-D Numerical Method - Abdul Rahman, Nazahah Nuha; Sanusi, Shahmir Hayyan; Kiow, Lee Woon (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research analyzes the vibration characteristic of several designs of crack classification by using the numerical modeling method by developing a wheel/rail contact model that simulates a wheel rolling on a track. The harmonic response of the railway vehicle wheelset is investigated by using ANSYS software. The findings and trends of the frequency response show the more lines of crack occurs on the rail, the highest value of amplitude changes. The influencing factors are due to the exposure of the contact surface area that has been exposed.